(3QSGdI aj MLjI GdXfs - (3cGTa GdZWGA, Ydj Hf LYaQ, J(B1253(3g`s ((3GdgGOj Hf GdYHGSs)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf(B...(3hHYO abO SCdfj HYV GdWdHI GdeMUdjf Cf CcJH QSGdI aj MLjI GdeXfI hGajI(B...s
(3BNQgG (B:s
(3hCeG HGdfXQ Edi GdTc hGdXf hGdhge ceG jbY cKjQG ef ZjQ eSJbje GdeRGL agh Xf hhge hTc(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B:(3L(B4(3,U(B269s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3CUhd Gdabgs